APLIKASI PEMILIHAN STRATEGI PROMOSI PENERIMAAN MAHASISWABARU POLITEKNIK NEGERI TANAH LAUT MENGGUNAKAN METODE K-MEANS CLUSTERING - Veri Julianto; Jaka Permadi; Noviyanti (Department of Science and Technology Ibrahimy University, 2017)
Politeknik Negeri Tanah Laut in order to improve the new student admission, has adopted numerous type of promotion strategies. The strategies are among others high school visits, banner displays, brochure distribution, and promotions via social media. However, those strategies adopted by Politeknik Negeri Tanah Laut are admittedly costly. Application of Selecting Promotion Strategy Enrollment of New Students in the Politeknik Negeri Tanah Laut is an application used to help determine what kind of promotional strategy is likely to be more accurate and more planned as the guidance as well as the reference in order to increase the enrollment percentage of new students. The determination of such promotional media’s outcomes is supported by applying the method of K-Means Clustering to do the classification of promotional media data obtained from the result of students’ questionnaires. Obviously such thing becomes a solution to help determine the promotional strategy at Politeknik Negeri Tanah Laut.